Comparison of Anti-Dengue Antibody Diagnostic Tests Using Immunochromatography and Fluorescence Immunoassay Methods at dr. Ario Wirawan Salatiga Pulmonology Hospital - Wahyuningtyas, Nunung Dartini; Puspitaningrum, Rioni Wahyu; Ahmad, Fariz Zulfikar; Asmarani, Dara Gita; Maula, Atya Rakhmatul (Smart Medical Journal, 2024)
Introduction: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus, which is transmitted through the bite of the Aedes aegypti. The agent is the dengue virus, which belongs to the Flaviridae family and Flavivirus genus, consisting of 4 serotypes, namely Den-1, Den-2, Den-3, and Den-4. Antibodies that appear generally are IgG and IgM. The methods used in examining dengue antibodies include Immunochromatographic (ICT) and Fluorescent Immunoassay (FIA) methods. The ELFA method is used for diagnostic testing.Objective: To determine whether there is a difference in anti-dengue antibody examination using ICT and FIA methods at the dr. Ario Wirawan Salatiga Pulmonology Hospital.Method: The type of research used is descriptive comparative with a cross-sectional method. This research was conducted from October to November 2023. 44 samples used in this study were examined for diagnostic tests using ELFA method, and then anti-dengue IgG and IgM were examined using the ICT and the FIA methodsResults: The results of the research showed that the sensitivity of IgG method and IgG of ICT method were 86.21% and 75.86%, respectively, and the specificity of the IgG of the FIA method and the IgG of the ICT method was 80.00% and 93.30% respectively. Meanwhile, the sensitivity of IgM by  FIA method and ICT method is 80.00% and 93.30%, respectively, while the specificity of IgM by  FIA method and IgM by  ICT method is 82.76%.Conclusion: There is a significant difference between examining anti-dengue antibodies using Immunochromatography (ICT) and Fluorescence Immunoassay (FIA) methods.